Carbon Tax and Its Impact on Economy in Indonesia - Dani Ramdani (Budapest International Research and Critics University, 2023)
The research problem raised in this study is what is the impact of the implementation of the carbon tax on climate change and carbon dioxide emissions and other impacts on the Indonesian economy. This research is important to do because the Indonesian economy has not recovered 100% but the state issued a new policy with a plan to implement a new tax which can increase the burden on companies / industries and can have an impact on increasing unemployment due to layoffs carried out by the company / industry. This research is motivated by several research results on climate change and carbon dioxide emissions where by 2050 it is predicted that the earth's temperature will get hotter and unhealthy air will kill many people due to increasing carbon dioxide emissions. The author tries to analyze what is the impact of implementing a carbon tax on the economy in Indonesia. The authors collected data on the implementation of carbon taxes in 15 countries that have already implemented it, namely from 1990-2019. The method used in this study is a descriptive qualitative approach.